2000
DOI: 10.1155/s1064744901000035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Clindamycin Vaginal Ovule (3‐Day Treatment) vs.Clindamycin Vaginal Cream (7‐Day Treatment) in Bacterial Vaginosis

Abstract: Objective:To compare the efficacy and safety of a 3-day regimen of clindamycin vaginal ovules with a 7-day regimen of clindamycin vaginal cream for the treatment of bacterial vaginosis (BV). Methods: Women with a clinical diagnosis of BV were treated with a 3-day course of clindamycin ovules or a 7-day course of clindamycin cream administered intravaginally. Three hundred and eighty-four patients received study drug and were included in the evaluable patient population (ovule group, n = 204; cream group, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 14 publications
0
22
0
2
Order By: Relevance
“…However, a prospective study of rural women in Gambia found no association between any sexual behavior and BV. A recent Meta-analysis found the epidemiological data to be consistent with BV having a sexual mode of transmission, but additional factors were likely to contribute to the risk [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…However, a prospective study of rural women in Gambia found no association between any sexual behavior and BV. A recent Meta-analysis found the epidemiological data to be consistent with BV having a sexual mode of transmission, but additional factors were likely to contribute to the risk [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The primary regimen for the treatment of BV is oral metronidazole,500 mg twice a day for 7 days.A single 2.0-g dose of metronidazole such as used to treat trichomoniasis is less effective and is not recommended [50].Vaginal preparations containing 0.75% metronidazole gel or 2% clindamycin cream or ovules containing 100 mg od clindamycin are effective and have few systemic effects [51][52][53].Treatment failure occur fairly commonly ,presumable because normal Lactobacillus-dominated flora fails to become established after anaerobes and other components of BV flora have been reduced in number with use of antimicrobial agents [54].Recent studies has shown that persistence of G.vaginalis in biofilims on the vaginal wall may associated with treatment failure [55].…”
Section: Treatment Of Bvmentioning
confidence: 99%
“…Alternative regimens include several tinidazole regimens (601) or clindamycin (oral or intravaginal) (602). An additional regimen includes metronidazole (750-mg extended release tablets orally once daily for 7 days); however, data on the performance of this alternative regimen are limited.…”
Section: Alternative Regimensmentioning
confidence: 99%